The gall wasp fauna of Iran (Hymenoptera: Cynipidae: Cynipinae): species checklist and biogeographical assessment - Tavakoli, Majid; Hosseini-Chegeni, Asadollah; Stone, Graham N.; Sadeghi, Seyed E.; Atkinson, R. J.; Melika, George (Zootaxa, 2021)
We provide a checklist of the gall wasps (Hymenoptera: Cynipidae: Cynipinae) of Iran, and place these records in a biogeographical perspective on three spatial scales, comprising (i) the Western Palaearctic, (ii) Western Asia (Turkey, the southern Caucasus and the Middle East) and (iii) regions within Iran. We present distribution and biological data for 121 species in 24 genera, representing nine of the 12 known cynipid gall wasp tribes. The most species–rich tribe in Iran is the oak gall wasp tribe Cynipini, with 74 species and 11 genera. Cynipid species richness is highest in the central and northern Zagros, with a distinctively different fauna in the forests along the southern shores of the Caspian Sea. Of the species found in Iran, 63 have distributions that extend westwards far into Europe, and can be considered Western Palaearctic species. Twenty four species comprise a distinct eastern component within the Western Palaearctic, with distributions that include Iran and some or all of Turkey, the Middle East and the Caucasus. Twenty one species are apparently endemic to Iran, with distinct Zagros and Caspian components. We highlight biological and phylogeographic processes that may underlie these patterns.